Orchid flora of Fraser's Hill, Malaysia - Nordin, Farah Alia Nordin (2012)
A diversity study of the orchids has been carried out in Fraser’s Hill and it was the first scientific study specifically on the diversity of orchids done in Fraser’s Hill. The main aim of this study is to produce a proper scientific documentation on the orchid flora of Fraser’s Hill and their current conservation status. Fourteen monthly field visits have been made to Fraser’s Hill from August 2009 until December 2010. A total of 191 species in 74 genera from 3 subfamilies were recorded. Ninety - two species in 16 genera are new records to Fraser’s Hill which 83 species were collected from field surveys and another 9 were gathered from unpublished herbarium specimens. From the account, seven species are new records to Malaysia and four to Peninsular Malaysia. The most outstanding feature of the orchids of Fraser’s Hill is they consist of both Malesian flora and Burmese – Thai element. Thirty – three species are recognized as endemic to Peninsular Malaysia including two species that were previously recorded only from Sumatra but were found in Fraser’s Hill; Bulbophyllum farinulentum and Dipodium conduplicatum. Taeniophyllum campanulatum, a species confined to Fraser’s Hill and previously claimed to be extinct was collected in this study. Through observations, resort development, road construction, natural disaster, local climate change and human disturbances were threats to the orchids and their habitats in Fraser’s Hill. From the conservation assessment conducted in this study, two species were proposed to be extinct locally; Corybas fornicatus and Dendrobium hymenopterum. Eighty species were identified as threatened species and 11 were treated as rare. Pine Tree Trail and Bishop Trail stand out for in – situ conservation sites in Fraser’s Hill because they houses the most diverse orchid species including the extremely rare species Dendrobium derryi and Macropodanthus alatus.